Locating Europe : a figure, a concept, an idea? - Gasché, Rodolphe (Studies in Continental thought., 2021)
"Is the idea of Europe outdated? The concept of European unity, the animating spirit of the European Union, seems increasingly fragile in the face of far-right populist movements. In Locating Europe , Rodolphe Gasché attempts to answer the question of how to think about Europe. Is it a figure, a concept, or an idea? Is there anything still compelling and urgent about the idea of Europe? By looking at phenomenologist and postphenomenological thinkers in the second half of the 20th century, Gasché reveals that Europe is more than just one geographical and cultural entity. The idea of Europe is based on common foundations: a distinctive conception of reason, of self-criticism, of responsibility, freedom, equality, human rights, and democracy, and it is these foundations that are under threat. In Locating Europe: A Figure, a Concept, an Idea? Gasché engages the philosophy of Hans-Georg Gadamer, Karl Jaspers, Karl Löwith, and others, focuses on the most significant philosophical representations of Europe, and explores the potential, and especially the limits, of the notion of Europe"--